DEVELOPMENT OF INTERACTIVE MEDIA FOR ASSESSMENT AND EVALUATION COURSES - Sugihartini, Ni Nyoman; Marvilianti Dewi, eka Dianita (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
This research aimed to develop and implement interactive media assessment and evaluation courses. Assessment and evaluation courses were the essential courses that students must master as prospective teachers. The development and improvement of content and media development of assessment and evaluation courses continued to be carried out to provide optimal academic services to students in online learning during the covid-19 pandemic. One alternative that could be done was to develop an interactive media-based articulate storyline that integrates with e-learning moodle. The model used in interactive media development was ADDIE (Analyze, Design, Development, Implementation, Evaluation). Based on curriculum analysis and syllabus of assessment and evaluation courses, then described into five learning activities, with the following description: (1) Learning activities 1: Basic concepts of evaluation and assessment, (2) Learning activities 2: Scale of measurement and Data Transformation, (3) Learning activities 3: Preparation of tests, (4)  Learning activities 4: Development of non-test jenin evaluation instruments, (5)  Learning activities 5: Analysis of test points and non-tests and examples of implementation. The five learning activities were designed with Computer Assisted Instruction (CAI) model. In its implementation in e-learning, each learning activity consists of several chapters. Then, each learning activity was equipped with Pdf files, animated videos, forums, individual tasks/projects, and articulate storyline-based interactive media.